FORMULATION OF STREPTOMYCES ANTAGONIST WITH INERT AND ORGANIC CHARGES AGAINST MYCOSPHAERELLA FOOT ROT AND BLIGHT (Sciences & Technologie. C, Biotechnologies, 2010)
Peas is highly susceptible to preemergence damping off, caused by Mycosphaerella pinodesin western Algerian regions. Rhizosphere actinomycetes which were antagonistic this pathogen was isolated from chellif soils. An isolate of Streptomyces(St7c5) provided superior seed protection. Increased in both the germination and plant growth were recorded following treatment of seeds with Streptomycesformulated with inert or organic charge when compared to control. Application of the antagonist agent resulted in a significant reduction of Mycosphaerellafoot rot to 5% compared tountreated seeds (30.5%). Application of Streptomycesresulted in a significant reduction of blight symptoms when compared to the control or when treated with talc alone. Hence, the talc formulation of Streptomycesagent can be recommended as one of the crop strategies for the management of foot rotting and blight caused by Mycosphaerella pinodes.